2018
DOI: 10.1155/2018/1654530
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetes and Relationship with Socioeconomic Status in the Thai Population: National Health Examination Survey, 2004–2014

Abstract: Objective To determine the prevalence and trend of diabetes, related glycemic control, and influential socioeconomic (SES) factors in the Thai population aged ≥20 years during 2004–2014. Methods Data from the Thai National Health Examination Survey 2004, 2009, and 2014 were used. Age-adjusted prevalence was calculated, and the associations of education levels with prevalence of diabetes and glycemic control were examined using logistic regression. Results Age-adjusted prevalence of diabetes increased from 7.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
126
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(142 citation statements)
references
References 20 publications
11
126
5
Order By: Relevance
“…This study found a high proportion of undiagnosed diabetes (41.9%), similar to findings among women in Thailand (41.3%) , but generally better than in China (69.8%) , Guinea (56%) , and Uganda (48.9%) . The proportion of diabetics receiving treatment in this study (40.3%) was higher than in China (25.8%) , but only 26.4% of those treated had adequate glycaemic control, vs .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This study found a high proportion of undiagnosed diabetes (41.9%), similar to findings among women in Thailand (41.3%) , but generally better than in China (69.8%) , Guinea (56%) , and Uganda (48.9%) . The proportion of diabetics receiving treatment in this study (40.3%) was higher than in China (25.8%) , but only 26.4% of those treated had adequate glycaemic control, vs .…”
Section: Discussionsupporting
confidence: 78%
“…The lower rate of diabetes found Laos compared to its neighbour Thailand may be explained by a younger age structure, lesser degree of urbanization and less extensive lifestyle change (e.g., still more physically active and lower rate of obesity) in Laos compared to Thailand [6]. This study found a high proportion of undiagnosed diabetes (41.9%), similar to findings among women in Thailand (41.3%) [6], but generally better than in China (69.8%) [7], Guinea (56%) [9], and Uganda (48.9%) [11]. The proportion of diabetics receiving treatment in this study (40.3%) was higher than in China (25.8%) [7], but only 26.4% of those treated had adequate glycaemic control, vs. 39.7% in China [7].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…All provincial laboratories were standardized to the central laboratory at the Department of Medical Service, Ministry of Public Health. In 2014, there were a total of 22,095 participants aged �20 years, and 8.8% adults had available blood samples [7].…”
Section: Design Settingmentioning
confidence: 99%
“…By disease burden, diabetes was the leading cause for men, and the seventh cause for women in 2014 [6]. The age adjusted prevalence of diabetes increased from eight to ten percent from 2004 to 2014 in Thailand [7].…”
Section: Introductionmentioning
confidence: 99%